Peningkatan Motivasi Belajar Peserta Didik pada Mata Pelajaran PKN Melalui Media Kartu Kuartet Pembelajaran di Kelas VII.3 SMP Negeri 10 Palembang - Windi Rahmadiani; Ardiansyah Saputra; Sri Artati Waluyati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Instructional media can be used by teachers to increase student learning motivation which is still low so that this research is the background to describe the use of Quartet Card learning media to increase student learning motivation in stage D, namely class VII.3 SMP Negeri 10 Palembang for the 2022 academic year. In 2023, where the condition of learning motivation is low when participating in Civics learning. This research was conducted using collaborative classroom action research methods with the McGregor technique. This quartet media has the advantage of being equipped with colorful and attractive images and is equipped with the application of quartet card game media on the material Respect for the Environment and Local Culture which is marked by a record of collecting assignments which increases regularly, namely in the pre-cycle there were 12 people who submitted assignments, cycle 1 there are 16 people who collect assignments and cycle 2 there are 32 people who collect assignments. The completeness of each cycle also increases.